2021
DOI: 10.4103/1995-7645.304293
|View full text |Cite
|
Sign up to set email alerts
|

Gender disparity in COVID-19: Role of sex steroid hormones

Abstract: The emerging pandemic of COVID-19 caused by the novel pathogenic human coronavirus SARS-CoV-2 has caused significant morbidity and mortality across the globe, prompting the scientific world to search for preventive measures to interrupt the disease process. Demographic data indicates gender-based differences in COVID-19 morbidity with better outcome amongst females. Disparity in sex-dependent morbidity and mortality in COVID-19 patients may be attributed to difference in levels of sex steroid hormones -androge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Among all patients examined in this present study, the majority of moderate or severe cases of COVID-19 involved male patients ( p = 0.014). As studies show the same male predominance [ 8 , 26 , 27 , 28 ], some hypotheses have been raised in an attempt to explain such prevalence, including mechanisms of cell protection mediated by the presence of female hormones, possible gender-related differences in immune responses, and even behavioural differences between men (e.g., smoking, which is more prevalent in male individuals) and women [ 29 , 30 , 31 ]. The higher prevalence of TTV-DNA in male individuals and in more severe cases is similar to the findings reported by other studies of individuals with different causes of immunosuppression [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among all patients examined in this present study, the majority of moderate or severe cases of COVID-19 involved male patients ( p = 0.014). As studies show the same male predominance [ 8 , 26 , 27 , 28 ], some hypotheses have been raised in an attempt to explain such prevalence, including mechanisms of cell protection mediated by the presence of female hormones, possible gender-related differences in immune responses, and even behavioural differences between men (e.g., smoking, which is more prevalent in male individuals) and women [ 29 , 30 , 31 ]. The higher prevalence of TTV-DNA in male individuals and in more severe cases is similar to the findings reported by other studies of individuals with different causes of immunosuppression [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biologically, hormones can influence the viral infection in host cells and impair the immune response to viral infection. Strogen may be protective against SARS-CoV-2 infection, while testosterone was associated with disease severity and high levels of serum cytokines in men [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that biological sex is a significant risk factor in COVID-19. This is likely due to physiological differences between males and females that can affect the severity of infection and autoimmune responses [ 12 15 ].…”
Section: Risk Factors For Acute Covid-19 and Pascmentioning
confidence: 99%